The role of owner/manager in adoption of electronic commerce in small businesses: the case of developing countries - Ghobakhloo, Morteza; Tang, Sai Hong (Emerald Group Publishing, 2013)
Purpose: Based on theories from the innovation diffusion literature, the purpose of this paper is to develop an integrated model of electronic commerce (EC) adoption in small businesses (SBs) of developing countries. The research model specifies variables at managerial level as the primary determinants to EC adoption in SBs. Design/methodology/approach: A questionnaire-based field survey was conducted to collect data from 268 owner/managers of SBs in Iran. The data were analysed using factorial analysis. Subsequently, six hypotheses were derived and tested by hierarchical multiple regression and logistic regression analysis. Findings: Perceived benefits, perceived compatibility, perceived risks, perceived costs, and innovativeness were found to be the significant determinants of decision to adopt EC. Likewise, discussion on discriminators between adopters and non-adopters of different EC applications has been provided. Research limitations/implications: Cross-sectional data of this research tends to have certain limitations when it comes to explaining the direction of causality of the relationships between the variables. The study focuses only on the manufacturing SBs of Iran. Practical implications: The research findings have important implications for practising managers, information systems experts, and policy-makers. Governments should follow specific policies to facilitate institutionalisation of EC in SBs. Similarly, EC vendors and technology providers should collaborate with SBs to enhance the compatibility of different EC applications with specific characteristics of these businesses. Originality/value: To the best of the authors' knowledge, this paper is perhaps one of the first that examines the adoption of EC by SBs in a developing country context, using a research model which tests the effects of owner/managers' attributes on adoption of simple and advanced EC applications.